Association of Inventory to Measure and Assess imaGe Disturbance – Head and Neck Scores With Clinically Meaningful Body Image-Related Distress Among Head and Neck Cancer Survivors - Macias, David; Hand, Brittany N.; Pipkorn, Patrik; Williams, Amy M.; Chang, Steven S.; Zenga, Joseph; Nilsen, Marci L.; Rhoten, Bethany A.; Huang, Andrew T.; Osazuwa-Peters, Nosayaba; Maurer, Stacey; Balliet, Wendy; et al. (Frontiers in Psychology, 2021)
Objective: The Inventory to Measure and Assess imaGe disturbance–Head & Neck (IMAGE-HN) is a validated patient-reported outcome measure of head and neck cancer-related body image-related distress (BID). However, the IMAGE-HN score corresponding to clinically relevant BID is unknown. The study objective is to determine the IMAGE-HN cutoff score that identifies head and neck cancer patients with clinically relevant BID. Methods: We conducted a cross-sectional study at six academic medical centers. Individuals > 18 years old with a history of head and neck cancer treated with definitive intent were included. The primary outcome measure was the IMAGE-HN. A Receiver Operating Characteristic curve analysis was performed to identify the IMAGE-HN score that maximized sensitivity and specificity relative to a Body Image Scale score of >10 (which indicates clinically relevant BID in a general oncology population). To confirm the validity of the IMAGE-HN cutoff score, we compared the severity of depressive (Patient Health Questionnaire-9 [PHQ-9]) and anxiety symptoms (Generalized Anxiety Disorder-7 [GAD-7]), and quality of life (University of Washington-QOL [UW-QOL]) in patients with IMAGE-HN scores above and below the cutoff. Results: Of the 250 patients, 70.4% were male and the mean age was 62.3 years. An IMAGE-HN score of > 22 was the optimal cutoff score relative to a Body Image Scale score of > 10 and represents a clinically relevant level of head and neck cancer-related BID. Relative to those with an IMAGE-HN score of < 22, patients with IMAGE-HN scores of > 22 had a clinically meaningful increase in symptoms of depression (mean PHQ-9 score difference = 5.8) and anxiety (mean GAD-7 score difference = 4.1) as well as worse social-emotional QOL (mean UW-QOL score difference = 21.5). Using an IMAGE-HN cutoff score > 22, 28% of patients had clinically relevant BID. Conclusions: An IMAGE-HN score of > 22 identifies patients with clinically relevant head and neck cancer-related BID. This score may be used to detect patients who could benefit from strategies to manage their distress, select patients for studies evaluating interventions to manage head and neck cancer-related BID, and improve our understanding of the underlying epidemiology of the disorder.